Nothingness Is All There Is: An Exploration of Objectless Awareness During Sleep - Alcaraz-Sánchez, Adriana; Demšar, Ema; Campillo-Ferrer, Teresa; Torres-Platas, Susana Gabriela (Frontiers in Psychology, 2022)
Recent years have seen a heightened focus on the study of minimal forms of awareness during sleep to advance the study of consciousness and understand what makes a state conscious. This focus draws on an increased interest in anecdotical descriptions made by classic Indian philosophical traditions about unusual forms of awareness during sleep. For instance, in the so-called state of witnessing-sleep or luminosity sleep, one is said to reach a state that goes beyond ordinary dreaming and abide in a state of just awareness, a state in which one is not aware of anything else other than one’s own awareness. Moreover, for these traditions, this state is taken to be the essence or background of consciousness. Reports on such a state opens the door to exciting new lines of research in the study of consciousness, such as inquiry into the so-called “objectless” awareness during sleep—states of awareness that lack an ordinary object of awareness. In this two-staged research, we attempted to find the phenomenological blueprints of such forms of awareness during sleep in 18 participants by conducting phenomenological interviews, informed by a novel tool in qualitative research, the micro-phenomenological interview (MPI) method. Following a phenomenological analysis, we isolated a similar phase across 12 reported experiences labelled as ‘nothingness phase’ since it described what participants took to be an experience of ‘nothingness’. his common phase was characterised by minimal sense of self—a bodiless self, yet experienced as being ‘somewhere’—, the presence of non-modal sensations, relatively pleasant emotions, an absence of visual experience, wide and unfocused attention, and an awareness of the state as it unfolded.